Caracterização do complexo teníase-cisticercose bovina em São João Evangelista/MG - Fabiana Leoncio Garro (2011)
This study was carried out to determine the situation of human taeniasis and bovine cysticercosis in the city of São João Evangelista, located in Guanhães, Minas Gerais. Serum samples was collected from 339 cattle in 15 randomly selected farms to perform ELISA and Immunoblot serological tests in order to diagnose cysticercosis, using vesicular fluid antigen (LVcra) from Taenia crassiceps. A socioeconomic questionnaire was filled in each property for the analysis of the factors that favor the maintenance of the complex. Additionally, there was the diagnosis of human taeniasis verified by stool examinations of the properties inhabitants. A prevalence of 4.1% for bovine cysticercosis and the frequency of 2.94% for human taeniasis was found . Among the risk factors, a statistically significant relation (p = 0.042) was found between the occurrence of bovine cysticercosis and the ingestion of undercooked meat. It was concluded that bovine cysticercosis is widely distributed in the city of São João Evangelista, with rates considered endemic, being it necessary to adopt controlling measures with continuous epidemiological and health surveillance.